Politik Hukum Pers Pada Masa Kolonial - Muhammad Zen Al-Faqih (Jurnal Pewarta Indonesia, 2025)
This research is about the legal politics of the press during the colonial period. The aim of this research is to understand legal politics in the colonial period, and to understand the political configuration in the colonial period, as well as to understand the legal products of that period. In the discussion section of this research, the political configuration during the Dutch East Indies era which was authoritarian was discussed. This kind of political configuration gives rise to press legal products that have a repressive and orthodox character. This research uses a normative juridical method using the concept of legal politics as a research conceptual framework. The use of this normative juridical method is necessary for the purposes of analyzing the content of legal products issued by the State based on the political configuration that existed at that time